Rancang Bangun Sistem Kontrol Keamanan Gerbang Menggunakan Raspberry Pi B+ Berbasis Web - Arief Saptono; Abdul Malik; Muhamad Satim (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
Computer and information technology from time to time are always experiencing developments, both in terms of hardware, software and the internet being one of the most important things atthis time. The increasing number of applications of computer technology will make the role of computers increasingly important to be more advanced (modernization). The security system isstill not effective and efficient enough, so that a control using a website is needed to help the security control process at the gate. This system is not only used in offices, but can be used inhome security, etc. So we need a security system, where the security control system uses a tool to monitor realtime security via a web browser, namely a webcam (Web Camera). A web-basedgate control system can be designed using the Raspberry Pi B +. From the explanation mentioned above, the researcher made a gate control device that was given to the Microcontroller using a Web Browser in order to open and close the gate. So it is hoped that this security system application can provide a sense of comfort, in addition, of course, with this system application it can reduce the number of crimes that occur both crimes and other crimes.